A multi-scaled demonstrator for aircraft weight and balance measurements based on FBG sensors: Design rationale and experimental characterization. (July 2019) - Brindisi, A.; Ameduri, S.; Concilio, A.; Ciminello, M.; Leone, M.; Iele, A.; Consales, M.; Cusano, A.
Highlights: Weight and Balance in aircraft. Design criteria of an on board weight and balance system. Sensing system based on fiber Bragg grating integrated in the landing gear system. Design and prototyping of a multi-scaled weight and balanced demonstrator for aircraft. Experimental characterization of the multi-scaled W&B demonstrator. Abstract: A multi-scaled W&B demonstrator able of reproducing the same loading condition of an aircraft as a whole is designed, manufactured and experimentally characterized. Two laws of similarity guided the design of the demonstrator, concerning geometrical and weight aspects. Total weight and center of gravity position, including payloads are calculated starting from strain measures with Fiber Bragg Gratings (FBG) sensors installed on the landing gear system.